Effective Pain Management in a Patient with Colon Cancer: A Case Report of Combined Quadratus Lumborum and Transabdominal Plane Blocks - Shallahudin; Ristiawan Muji Laksono; Taufiq Agus Siswagama; Aswoco Andyk Asmoro; Buyung Hartiyo Laksono (HM Publisher, 2025)
Cancer-related pain, particularly in cases of advanced colon cancer, presents a significant challenge to healthcare providers. Traditional pain management strategies, including opioids, often prove inadequate or are associated with undesirable side effects. Quadratus lumborum block (QLB) is an emerging regional anesthesia technique offering potential benefits in managing abdominal pain. This case report describes the successful implementation of combined QLB and transabdominal plane (TAP) blocks for effective pain management in a patient with colon cancer. A 53-year-old male patient with a history of colon cancer presented with severe abdominal pain at the site of his stoma radiating to his back. The pain was exacerbated by movement and significantly impacted his quality of life. Despite receiving a multimodal analgesic regimen, including a fentanyl patch and oral medications, his pain remained poorly controlled. After careful consideration, a combined QLB and TAP block was performed using ultrasound guidance. Following the procedure, the patient experienced significant pain relief, with his Numerical Rating Scale (NRS) score decreasing from 7-9 to 1-2 at rest and from 5-6 to 2-3 during movement. He reported no nausea or vomiting and was able to mobilize comfortably. This improvement in pain control facilitated his recovery and enhanced his overall well-being. In conclusion, this case report highlights the potential of combined QLB and TAP blocks as an effective pain management strategy for patients with colon cancer. This approach may offer a valuable alternative or adjunct to traditional methods, particularly in cases where opioid use is limited by side effects or tolerance. Further research is warranted to investigate the long-term efficacy and safety of this technique in a larger patient population.